O que é um homem?: Estudo psicanalítico söbre a masculinidade a partir do discurso de homens penectomizados por câncer de pênis - Oliveira, Luciano Lima de (2020)
From a practice clinic with men undergone to the surgical amputation of the penis (penectomy), some questions arose and resulted, initially, in our Master research in Psychology. Some of the findings helped us to formulate our PhD research problem, which can be resumed in the following question: “What is a man?”. We have observed in the patients discourse that the psychological suffering is not only due to the body modification but also to the necessity of facing the reality of the amputation through the construction of new answers to the question of what a man is, in special, a man without the penis. The general objective of the research was to contribute to the debate on the masculinity in the psychoanalysis, from the discourse of men undergone to the penectomy, as well as the psychoanalytic theorizations about the masculinity. Regarding to the specific objectives they were:(1) to identify in Freud’s and Lacan’s work, in addition to other contemporaneous authors, the elements that allow us to think the masculinity in a psychoanalytic perspective; (2) to understand, from our research subjects discourse, the penile amputation impact on the masculinity; (3) to verify the new support points, if they do exist, to the patients masculinity in the absence of the penis. In order to achieve these objectives, we, initially, searched and discussed on Freud’s and Lacan’s work the necessary elements to a psychoanalytic reflection about the masculinity. Next, we retook the interviews made at the time of our Master in Psychology research in order to verify what they could teach us in regard to the transformations occurred in the masculinity when it loses the its penile support. We worked on the interviews with the viewpoint of the relationship that each of our subjects sets up with the significant. Therefore, the decryption of the arisen significants took into account the unconscious dimension, which commands the discourse of the significant chain. Among the results of the research we emphasize: (1) In Freud’s work, the masculinity is closer to a defensive construction against the feminization regarding to the father, what implies the castration; (2) The last teaching of Lacan allows us to consider the masculinity as a singular creation facing the impossible of signifying concerning to the sexed being;(3) The subjects’ resistances in following the medical discourse prescriptions on how to satisfy a woman after the penectomy are due to the incompatibility of these injunctions and the semblances that have always served as anchor points to these subjects’ virile image; (4) after the surgery, new significants, such as “the gentle man” and “the family protector”, take part in the psychological reconstruction work of the virile image. We expect that our research may contribute to the enrichment of the debate on what being a man is, as well as to an in-depth comprehension of the masculinity by both the psychoanalysts and the health professionals that deal with men in general and in particular with those undergone on the penectomy.